Optimal reactive power dispatch: a review, and a new stochastic voltage stability constrained multi-objective model at the presence of uncertain wind power generation - Mohseni-Bonab, Seyed Masoud; Rabiee, Abbas (IET generation, transmission & distribution, 2017)
In this paper, a comprehensive review of recent researches carried out in the area of optimal reactive power dispatch (ORPD) is presented. The literature review consists of a classification of ORPD problem, along with a survey on the strengths and weaknesses of different models proposed previously. Also, a stochastic multi-objective ORPD (SMO-ORPD) model is studied under load and wind power generation uncertainties. A two-stage stochastic model is employed for dealing with the uncertainties. The considered objective functions are real power losses (PLs) and operation & maintenance (O&M) cost of wind farms (WFs). The proposed SMO-ORPD problem is solved by considering voltage stability index (i.e. Lmax index). Besides, ɛ-constraint technique and fuzzy satisfying approach are employed to pick up the best compromise solution. Two cases are considered as follows: (i) voltage stability relaxed SMO-ORPD, and (ii) voltage stability constrained (VSC) SMO-ORPD. In this study, reactive power compensation devices are modelled as discrete control variables. Hence, the proposed SMO-ORPD problem is modelled as a mixed-integer non-linear programming optimisation problem. The SMO-ORPD problem is implemented in GAMS environment, and it is examined on the IEEE 30 and 118-bus test systems. The numerical results substantiate that in the case of VSC-SMO-ORPD, active PLs are higher than the other case, whereas O&M cost of WFs is not different considerably.